A defense of utilitarian policy processes in corporate and public management - Brady, F. Neil (Journal of business ethics, 1985)
The growing awareness that corporate and public policy forming processes are intensively utilitarian has provoked a variety of criticism. The procedural difficulties of utilitarianism are well known; less well known but potentially more devastating is a set of charges that utilitarian policy processes intrude upon important relationships and societal processes. This paper defends utilitarian methods against these charges., More specifically, two criticisms are singled out for examination. The first is the claim that utilitarian policy processes systematically discriminate against the rights of non-human life and suppress any feelings of sympathy or obligation humans might have for animals or plants. The second is the argument that utilitarianism ultimately circumvents considerations of process which are essential for the development of individual and societal identity., Given these criticisms, the goal of this paper is to defend the role of utilitarian techniques in corporate and public policy processes against such charges.